2010
DOI: 10.3109/13685531003657776
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and bone turnover in male masters athletes aged 40–64

Abstract: We evaluated areal bone mineral density (aBMD), bone mineral content (BMC), and markers of bone turnover in male competitive masters athletes representing different training profile in the past and at present, aged 40-64 (14 endurance runners, and 12 speed-power athletes), and non-sport controls (n = 13). Dual-energy X-ray absorptiometry measurements of total body and regional aBMD, BMC and soft tissue composition were acquired. Serum concentrations of osteocalcin (OC), C-terminal crosslinking telopeptide of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 42 publications
2
25
1
1
Order By: Relevance
“…jumping/sprinting) versus endurance (i.e. cross-country running) athletes [3739]. In addition to having an enhanced background skeletal phenotype, jumpers exhibited side-to-side differences between their jump and lead legs at both the tibial diaphysis and distal tibia, with differences at the former site being greater than dominant-to-nondominant leg differences in cross-country runners.…”
Section: Discussionmentioning
confidence: 99%
“…jumping/sprinting) versus endurance (i.e. cross-country running) athletes [3739]. In addition to having an enhanced background skeletal phenotype, jumpers exhibited side-to-side differences between their jump and lead legs at both the tibial diaphysis and distal tibia, with differences at the former site being greater than dominant-to-nondominant leg differences in cross-country runners.…”
Section: Discussionmentioning
confidence: 99%
“…A single study to date has directly compared serum IGF-I in masters' athletes with controls [18], where the authors outline a lack of difference between endurance runners, speed-power athletes compared with moderately active controls. However, comparisons between masters' athletes and sedentary aging men have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in line with those reported by Sanada et al [15] who demonstrated significantly higher BMD values in the ribs and lumbar spines of young and old rowers than in their control group. Some investigators have shown that athletes, after many years of training or after the end of their sports career, have higher BMDs and greater bone strength at the sites exposed to the greatest load as compared with their non-active controls [4,5,19,20]. In our previous study on male track and field athletes, we found that the aBMD values of the whole skeleton and the regions examined (spine, trunk, pelvis, arms, and legs) as well as the BMC values (total-body, arms, trunk, and legs) were significantly higher in speed-power athletes compared with endurance athletes or control subjects [4].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have shown that athletes, after many years of training or after the end of their sports career, have higher BMDs and greater bone strength at the sites exposed to the greatest load as compared with their non-active controls [4,5,19,20]. In our previous study on male track and field athletes, we found that the aBMD values of the whole skeleton and the regions examined (spine, trunk, pelvis, arms, and legs) as well as the BMC values (total-body, arms, trunk, and legs) were significantly higher in speed-power athletes compared with endurance athletes or control subjects [4]. Korhonen et al [5] in a study examining systematically trained sprinters also showed greater bone strength, particularly bending rigidity in the anteroposterior plane, in comparison with a younger, physically active reference group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation